Obshhaja struktura processa mnogoletnej podgotovki sportsmenov, specializirujushhihsja v sportivnoj bor'be, i osnovy ih silovoj podgotovki - Manolaki, V. (Science in Olympic Sport, 2020)
The study of the sports careers of prominent athletes who became winners of the World Championships and the Olympic Games in freestyle and Greco-Roman wrestling, judo has allowed to characterize the general structure of long-term preparation process and competitive activity in these sports events. The generalization of the obtained material showed the presence of two stages in the long-term career of athletes. The fi rst covers the period from the beginning of sports engage-ment to reaching the level of higher achievements - 11 years - from 10 to 22 years. This is followed by the second stage of a long-term sports career, with an average duration of 6 years (up to the age of 28) with an extremely wide range of individual fl uctuations. Moreover, in some athletes (such as Fabio Basile), this stage may not occur at all due to the end of their career after achieving the highest result. In other athletes, it can last for 10 years or more, and in some of them (for instance, Aleksandr Mykhailin) - for 18 years. Each of the stages is characterized by a specifi c structure, which is based on the implementation of sports training principles.